Analisis Kelayakan Usaha Pengolahan Ikan Layang Kering di UD. Mutiara Laut Desa Sumberanyar Kabupaten Probolinggo - Ismi Jazila; Ramli Ramli (Faculty of Science and Technology University Ibrahimy, 2021)
The purpose of this study was to analyze the business feasibility of the dried scad mackerel (Decapterus spp.) processing At UD. Mutiara Laut. This research uses the case study method and was conducted in February 2020. The data collection method uses observation and interviews with business owners. The data used are primary and secondary data. The results showed that the profits of the dried scad mackerel processing at UD. Mutiara Laut in one month amounting to IDR 63,887,479. R / C ratio of 1.08. This means that the dried scad mackerel processing at UD. Mutiara Laut is profitable and feasible to be developed.